Rethinking food crisis responses: The Nigeria presentation of IFPRI's 2023 Global Food Policy Report & the launch of the CGIAR Research Initiative on Fragility, Conflict & Migration (FCM) - Carrillo, Lucia; Kosec, Katrina; Onilogbo, Omobolanle; Smart, Jenny; Ambler, Kate; Andam, Kwaw S.; Anisimova, Evgeniya; Edeh, Hyacinth O.; Fasoranti, Adetunji; Mugisho, Aline (International Food Policy Research Institute, 2023)
The purpose of this report is to describe work presented and discussions resulting from an event jointly convened by the CGIAR Research Initiative on Fragility, Conflict, and Migration (FCM) and the International Food Policy Research Institute (IFPRI) in Abuja, Nigeria on May 11, 2023. The event, titled “Rethinking food Crisis Responses,” drew many participants from Nigerian civil society, government, and the private sector, in addition to representatives of international organizations, local and international NGOs, and the donor community. This report was prepared by researchers from CGIAR, FCM, and IFPRI, reflecting on the insights shared, lessons learned, and collective discussions of the optimal next steps .